Registration of Four Postflowering Drought‐Tolerant Grain Sorghum Lines with Early‐Season Cold Tolerance. Issue 3 (16th August 2018) - Burke, John J.; Emendack, Yves; Hayes, Chad; Xin, Zhanguo; Burow, Gloria
Abstract : Four sorghum ( Sorghum bicolor L.) germplasm lines—PSLS‐SGCTB01 (Reg. No. GP‐842, PI 685009), PSLS‐SGCTR02 (Reg. No. GP‐843, PI 685010), PSLS‐SGCTB03 (Reg. No. GP‐844, PI 685011), and PSLS‐SGCTB04 (Reg. No. GP‐845, PI 685012)—were developed by the USDA–ARS in Lubbock, TX. The primary purpose for the release of these lines is to provide an alternative germplasm choice with superior early‐season cold tolerance stacked with postflowering drought tolerance based on the stay‐green trait. The PSLS‐SGCTB01 and PSLS‐SGCTR02 germplasm lines originated from the plant introduction PI 452605, PSLS‐SGCTB03 arose from the plant introduction PI 452808, and PSLS‐SGCTB04 arose from the plant introduction PI 452707. Lines derived from selected PI germplasm were evaluated in 2015 and 2016. Comparison of leaf and plant death ratings between BTx642 (stay‐green check), SC‐1506 (non‐stay‐green check), and the four developed lines with Ethiopian germplasm were determined for plants under irrigated, preflowering, and postflowering drought treatments. The four lines were also evaluated for final germination percentages and vigor ratings for field cold tests performed in 2015 and 2016. For public and private breeders, these new germplasm lines are an additional source for improving abiotic stress tolerance in diverse sorghum production environments.